The role of passion, satisfaction of needs and conflict in the perception of burnout in athletes - Reza Nikbakhsh (Islamic Azad university, Isfahan Branch, 2022)
Objective: The general purpose of the present study was to investigate the role of passion, satisfaction of needs and conflict in the perception of burnout in athletes.Methodology: The current research was a descriptive correlational research based on structural equation modeling, and the data was collected in the survey and through a questionnaire. The statistical population of this research was made up of all volleyball players aged 13 to 17 in Tehran, whose number was 295. In this research, the questionnaires of passion (Wallerand et al. 2003), satisfaction of needs in sports (Lopez et al. 2020), conflict (Wallerand et al. 2010), athlete burnout (Raedeke and Smith, 2001) were used.Results: The results showed that adaptive passion has a significant negative effect on conflict in athletes. While harmonious passion has a significant positive effect on the satisfaction of needs in athletes. Also, obsessive passion has a significant positive effect on conflict in athletes. While extreme passion has a significant negative effect on the satisfaction of needs in athletes. In addition, contrast has a significant positive effect on attrition in athletes. Satisfaction of needs has a significant negative effect on burnout in athletes.Conclusion: Basic psychological needs should be considered as the necessary energy to help actively engage with the environment, develop skills and healthy growth. Because when players receive more positive energy from attending training and matches and have a desire for more active interactions in training and match environments, in this case, their burnout rate will decrease.